Novelties In Banking Sphere and A Practice of Introducing Them into The Banking System of Uzbekistan - Eldor Uskanov Erkinovich (Zien Journals, 2022)
Today, the digital economy in general and, in particular, the digitalization of the banking and financial sector are in demand to increase the competitiveness of the national economy. The article reveals the features of digital banks and analyzes the problems and trends of their development in Uzbekistan.
Keywords: banking system; digital bank; digitalization; digital economy